2017
DOI: 10.1186/s41182-017-0047-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Lymphatic Filariasis Control Program towards elimination of filariasis in Vanuatu, 1997–2006

Abstract: BackgroundLymphatic filariasis (LF) occurs when filarial parasites are transmitted to humans through mosquitoes. The filarial worms affect the lymphatic system which leads to abnormal enlargement of body parts, chronic pain, disability, and social discrimination. In 1999, a commitment was made to eliminate LF from the Pacific Region by 2010. The Pacific Program to Eliminate LF began, with Vanuatu being one of the 16 endemic countries included in this program.MethodsIn 1997/1998 a LF prevalence baseline survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…LF is a heterogeneous disease with regard to gender, age and geographical distribution [11,[15][16][17][18]. Exposure to mosquitoes varies greatly depending on proximity to larval habitats, rainfall and temperature (for which altitude may be a proxy).…”
Section: Introductionmentioning
confidence: 99%
“…LF is a heterogeneous disease with regard to gender, age and geographical distribution [11,[15][16][17][18]. Exposure to mosquitoes varies greatly depending on proximity to larval habitats, rainfall and temperature (for which altitude may be a proxy).…”
Section: Introductionmentioning
confidence: 99%
“…military recruits, hospital patients, and blood donors) for microfilaraemia, antigenaemia, or antibodies [ 16 ]. For example, in Togo [ 21 ] and Vanuatu [ 22 ], nationwide LF surveillance has been successfully conducted by screening blood smears collected for malaria diagnosis. However, there is currently little evidence about the effectiveness of these strategies for identifying infected persons in the post-MDA setting.…”
Section: Introductionmentioning
confidence: 99%
“…The district health teams expected that all drugs distributed were consumed, however follow up research showed that only a proportion of recipients actually consumed the distributed LF drugs [ 13 ]. According to the international guidelines, LF drugs should be consumed using DOT [ 14 ]. In the Indonesian context, this would mean taking the pills in front of the cadres or the frontline health personnel .…”
Section: Introductionmentioning
confidence: 99%